Sensitivity of Liquidity, Investment Decision, and Financial Constraints - Hidayat, Riskin; Wahyudi, Sugeng; Muharam, Harjum (The Indonesian Capital Market Review, 2018)
This research aims to test the sensitivity level of liquidity and investment opportunity to investment decision between non-financially and financially constrained firms. The sampleon this research is the firms of Jakarta Islamic Index listed on Indonesia Stock Exchange from period 2011 to 2015. There are 13 sample firms obtained with 65 observations. This research uses moderating regresssion analysis. Independent variable is liquidity and investment opportunity, dependent variable is investment decision, moderating variable is financial constrains, and variable control is debt.This research classifies non financially constrains (NFC) and financial constrains (FC) firms into four steps by observing dividend policy, cash flow, debt (leverage), and investment opportunity. The result of research refers that liquidity and investment opportunity have a positive influence to investment decision. Liquidity is more sensitive to investment decision for financially constrained firms. Investment opportunity is more sensitive to investment decision for non-financially constrained firms. The result of robbusness test using sample of the firms LQ 45 period 2011 to 2015 with 23 sample firms obtained with 115 observations also shows the same result and consistent with sample firms in Jakarta Islamic Index.